Mismatch‐induced growth reductions in a clade of Arctic‐breeding shorebirds are rarely mitigated by increasing temperatures. (16th December 2021) - Lameris, Thomas K.; Tomkovich, Pavel S.; Johnson, James A.; Morrison, R. I. Guy; Tulp, Ingrid; Lisovski, Simeon; DeCicco, Lucas; Dementyev, Maksim; Gill, Robert E.; ten Horn, Job; Piersma, Theunis; Pohlen, Zachary; et al.
Abstract: In seasonal environments subject to climate change, organisms typically show phenological changes. As these changes are usually stronger in organisms at lower trophic levels than those at higher trophic levels, mismatches between consumers and their prey may occur during the consumers' reproduction period. While in some species a trophic mismatch induces reductions in offspring growth, this is not always the case. This variation may be caused by the relative strength of the mismatch, or by mitigating factors like increased temperature‐reducing energetic costs. We investigated the response of chick growth rate to arthropod abundance and temperature for six populations of ecologically similar shorebirds breeding in the Arctic and sub‐Arctic (four subspecies of Red Knot Calidris canutus, Great Knot C . tenuirostris and Surfbird C . virgata ). In general, chicks experienced growth benefits (measured as a condition index) when hatching before the seasonal peak in arthropod abundance, and growth reductions when hatching after the peak. The moment in the season at which growth reductions occurred varied between populations, likely depending on whether food was limiting growth before or after the peak. Higher temperatures led to faster growth on average, but could only compensate for increasing trophic mismatch for the population experiencing the coldest conditions. We did not find changes in the timing of peaks in arthropod availability across the study years, possibly because our series of observations was relatively short; timing of hatching displayed no change over the years either. Our results suggest that a trend in trophic mismatches may not yet be evident; however, we show Arctic‐breeding shorebirds to be vulnerable to this phenomenon and vulnerability to depend on seasonal prey dynamics. Abstract : Trophic mismatches between the timing of animal reproduction and the emergence of resources are expected to result in slower growth of offspring, but this is not always the case. Such variation in the effect of mismatches could be caused by mitigating factors, including increasing temperatures which can alleviate energetic costs for offspring. We show that later hatch dates (relative to the local food peak) led to reductions in chick body condition in five populations of Arctic‐breeding shorebirds. Although higher temperatures led to a higher condition, this could only compensate for later hatch in the population experiencing the coldest conditions, Red Knots ssp. islandica .